On the moment characteristics for the univariate compound poisson and bivariate compound poisson processes with applications (2013)
The univariate and bivariate compound Poisson process (CPP and BCPP,respectively) ensure a better description than the homogeneous Poisson processfor clustering of events. In this paper, new explicit representations ofthe moment characteristics (general, central, factorial, binomial and ordinarymoments, factorial cumulants) and some covariance structures are derivedfor the CPP and BCPP. Then, the skewness and kurtosis of the univariateCPP are obtained for the first time and special cases of the CPP are studiedin detail. Applications to two real data sets are given to illustrate the usageof these processes.